Guidelines on the Management and Prevention of Prediabetes - The Indonesian Diabetes Association The Indonesian Diabetes Association (Acta Medica Indonesiana, 2014)
Pandemic obesity and diabetes mellitus (DM), particularly type-2 DM (T2DM) now has become a serious threat for people worldwide. The International Diabetes Federation (IDF) suggests that the prevalence of DM in the world is 1.9% and it has made DM as the 7th leading cause of death worldwide. It has been estimated that the prevalence of diabetes between 1994 and 2010 was projected as much as 215.6 milion people; however an evaluation in 2007 revealed that the number of diabetic patients has reached 246 million people and it has been concerned that the number would increase in 2025 reaching more than 300 million people. Patients with DM may have various complilcations, including macrovascular diseases (heart disease, stroke and peripheral vascular disease) and microvascular diseases (retinopathy, neuropathy and nephropathy). Complications of DM have started early before the diagnosis of DM has been made. About 50% of patients have alreadly had one chronic complication at the time of diagnosis. Therefore, it is necessary to have a guideline on management of prediabetes condition associated with prevention of chonic complication and cardiovascular risk of diabetes. The guideline is expected to improve the skills of health care professionals in recognizing prediabetes condition, identifying people at high risk for diabetes and providing an appropriate management so that the incidence and complication of DM can be reduced.